Promotional activities at Bahagia Mendawai Library Bansir Laut Village Pontianak Tenggara District - Khofifah Nurhidayah; Atiqa Nur Latifa Hanum (Record and Library Journal, 2022)
Background of the study: Bahagia Mendawai Library wants to empower the community in the Kampung Wisata Caping Pontianak, which is on the outskirts of the Kapuas River. Purpose: To introduce the existence and benefits of libraries to the community, efforts are made through library promotional activities. Method: This study uses a qualitative descriptive method. Collecting data through observation, interviews and documentation. The number of informants consists of 4 (four) people. Findings: The results showed that the promotional activities carried out by the Bahagia Mendawai Library used publications using social media and brochures, participated in exhibitions and had various innovation programs such as Siberliterasi, JeLi, and Pojok Literasi. The media used are print media and the internet. The perceived obstacle are the lack of available resources in the form of inadequate facilities in carrying out promotional activities on social media and the weak knowledge of librarian related to promotions. Conclusion: The promotional activities carried out by the Bahagia Mendawai Library in terms of its existence are quite good because the library is already known by the community around the library and attracted the interest of people outside the Kampung Wisata Caping Pontianak. However, in terms of the usefulness of the promotion, it has not been maximized because not all people have used the library.